Inseminação artificial intra-uterina transcervical assistida por endoscopia em cadelas da raça Retriever do Labrador - Sabrina Pereira Macedo (2009)
The aims of the present study were to describe endoscopic transcervical intrauterine artificialinsemination (AI) technique in bitches, investigate its viability and difficulties; evaluatepregnancy rate and litter size; and evaluate behavioral and reproductive parameters, as vaginalcytology and serum progesterone assays, to determine time of insemination. Ten LabradorRetriever bitches were submitted to three endoscopic transcervical intrauterine AIs (with 48hintervals), using fresh canine semen. Oestrus and ovulation period were established by behaviorevaluations, progesterone assays and vaginal cytology, enabling AIs in optimal timing duringoestrus. During AI technique execution, the following aspects were evaluated: cervical oscatheterization difficulty, semen deposition resistance, occurrence of semen backflow, and timerequired to perform the AI. It was concluded that endoscopic transcervical intrauterine AItechnique was viable in Labrador Retriever bitches. The rigid cystourethroscope and sheathused fit to perform this technique. The methods employed to evaluate behavioral andreproductive parameters during the estrous cycle were effective to determine time of AI. Serialserum progesterone assays enabled determination of LH surge day, and thus ovulation.Pregnancy rate was 90 % (9 in 10 bitches). Mean litter size was 5,0 ± 2,6 puppies. These resultswere satisfactory in comparison with previous studies using transcervical intrauterine AI.